297 Chest Wall Chondrosarcoma in the Young. (11th January 2018) - Chakraborty, Baidarbhi; Ali, Sayed; Bakhos, Charles; Kozin, Scott; Balasubramanian, Manjula; Khurana, Jasvir
Abstract: Objectives: Chondrosarcoma of the chest wall accounts for about 15 % of all chondrosarcomas. It is exceedingly rare in the young. We present three such cases. Results: Case 1: A 48-year-old man presented 8 years ago with right lower anterior chest wall mass. Following a biopsy, a portion of chest wall was excised. The sixth rib had a sessile exophytic mass, which showed a Grade 2 chondrosarcoma (3.0 cm) arising from an osteochondroma (1.9 cm). The patient subsequently had right lung metastases resected in 2011, and a recent CT chest shows a new 2.2 cm nodule. Case 2: A 15-year-old male patient with multiple hereditary exostoses presented with a left supraclavicular exostosis in 2010, which was excised, and multiple fragments of pink-white bone and hemorrhagic soft tissue measuring 12.4 x 8.4 x 2.7 cm were submitted. The diagnosis was grade 1 chondrosarcoma, arising on osteochondroma. The patient recently presented with pain in left hip region. An MRI showed numerous osteochondromas involving the pelvic bones and proximal femur with one that is located in the left posterolateral ischium with a heterogeneous cartilage cap measuring 1.9 cm maximum thickness. Case 3: An 18-year-old woman who presented with an incidentally identified expansile anterolateral rib lesion with central calcifications typical for a chondroid matrix, and cortical thinning/erosion superiorly. Excision showed a hemorrhagic pink tan mass measuring 3 x 2.3 cm with a firm white-gray cut surface. Histologically, it was low-grade cartilage with areas of cortical scalloping and destruction along with permeation of the medullary space with bone entrapment, consistent with grade 1 chondrosarcoma. Conclusion: We present three rare cases of chondrosarcoma involving the ribs and clavicle and presenting in young patients. All three patients are alive; two have developed metastatic disease.